Efektivitas Model OMS (On Media Social) Dalam Meningkatkan Minat Studi Lanjut - Suwandono, Rudy; Sartinah, Endang Pudjiastuti; Purwoko, Budi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
This study discusses the implementation of the OMS (On Social Media) model of treatment in classical guidance services for students with an interest in further study in college. Aims to test the difference in effectiveness between the two treatment groups to increase interest in further study for class XII students at SMA Negeri 1 Bluto. This research is a quantitative study with a Quasy Experimental design, there are a control group and an experimental group. The sample uses purposive sampling, namely students who have a high score for lack of interest in further studies of 60 students who are divided into 2 treatment groups. The research instrument is a questionnaire that has been validated and supported by data sources, namely interviews, observations, and documentation. Data analysis using Paired T-Test, normality test method using Shapiro-Wilk, and homogeneity test using the Test of Homogeneity of Variances. The results of the normality test are normally distributed, which are classified as parametric, the results of the homogeneity test of all groups are homogeneous, while the results of the Paired T-Test test are differences in the increased interest in further studies after receiving treatment compared to before treatment, and the classical guidance treatment of the CSO model is effective in increasing interest in further studies. The use of the CSO model should be recommended as a method of providing services to students.